Academic & Managerial Talent in Universities: Examining the Applicability of Talent Management - Filiz Akar (Anı Publishing, 2019)
The aim of this research is to define academics' and managerial talent in the university and to examine the applicability of talent management according to administrators' experience and views. In this study basic qualitative research method was used. Participants determined by purposeful sampling method and study group consists of 15 faculty members-administrators from three public universities. Data were collected through interviews and analyzed by content analysis technique. Findings show that talented academics' characteristics exhibit an integrated structure based on merit, high intellectual competencies, personality, values, harmony, attitude towards work themes; talented managers' characteristics were collected under the themes of communication-motivation, managerial competencies, scientific competencies, personality and managerial values. It has also been revealed that talent management is necessary and useful in higher education but applicability depends on some regulations, positive work environment is important variable for attracting and retaining talent and situation in central and provincial universities is differentiated. Identification of future talents-potentials; organizing talent management and academic leadership programs, development of socio-cultural opportunities of the city that will attract talented academics through university-local administrations collaborations, systematic examination of academics' views on job satisfaction and positive working conditions can be recommended.